Site specific nutrient management for bitter gourd (Momordica charantia L) - Neenu.S (Department of soil science & Agricultural Chemistry, College of Agriculture, 2013)
A study entitled ‘Site specific nutrient management for bitter gourd (Momordica charantia L.) was conducted in College of Agriculture, Vellayani during 2007-12 with the objective of formulating a site specific nutrient recommendation for enhancing the bitter gourd production in Kalliyur village of Kerala. The experiment set up included three steps namely Omission trial, SSNM field study and validation of results. All the experiments were conducted in farmer’s fields of Kalliyur village. Kalliyur village, located in Thiruvananthapuram district with an area of 17.23 km 2 is one of the major vegetable growing tracts and bitter gourd is a popular vegetable in the locality. Spatial variability studies conducted revealed that remarkable variations existed in the soil properties across the village. Data on irrigation water analysis showed that the water used for irrigation was slightly acidic but safe for irrigation as it did not contain significant amount of soluble salts and other elements. Nutrient omission trial conducted in a farmer’s field at selected location showed that the indigenous supply of major nutrients in the locality is limited. The growth and yield parameters were the highest in (+) NPK treatment. Though the highest yield was recorded in (+) NPK plots, yield reduction in P omission plot was less compared to N and K omission owing to the higher supply of indigenous P in soil. The SSNM experiment revealed that site specific nutrient recommendations for high yield target with soil application of micronutrients recorded the highest values for all the growth and yield attributes of bitter gourd. Nutrient uptake and harvest index were also the highest in this treatment. The lowest value of harvest index was recorded by absolute control. In the case of nutrient balance sheet the highest value of N and K balance sheet was obtained in site specific nutrient recommendations for high yield target with soil application of micronutrients while the highest value of P balance sheet was obtained in farmer’s practice II. The correlation study revealed that bitter gourd yield was highly correlated with nutrient uptake as well as dry matter production and harvest index. Economic analysis showed that the SSNM practice is beneficial to farmers as it is able to provide more income than the usual farmer’s practice. The validation trial of the best treatments SSNM treatments with high yield target showed that the yield increase was consistent and hence can be prescribed to other farmers in Kalliyur village. The study thus conclusively proved that the present rates of fertiliser recommendation are not at all sufficient for getting maximum yield and profit to farmers. A site-specific nutrient prescription of 123: 59: 160: 30: 40: 25: 10 kg N P K Ca Mg Zn B ha -1 was found to produce 24 t of fruits ha -1 and a dose of 123: 59: 160: 30: 40 kg N P K Ca Mg + 1 per cent Zn foliar + 0.5 per cent B foliar ha were found to yield 22 t fruits ha -1 . The farmers in the area could get a monetary benefit of 601604/- and 542104/- ha -1 respectively by adopting these recommendations. Adoption of SSNM prescriptions is advantageous not only from the point of view of increasing profitability to farmers but also minimizing environmental degradation.